Model Pelatihan Step-by-Step Onsite Teacher Taining (SSOTT) dan Optimalisasi Kinerja Guru Membelajarkan Matematika di SD - Sugeng Utomo (Jurnal Aplikasi Manajemen, 2011)
The very least of teacher training result which can applied in the school cause many people doubt abaut the effectiveness of those teacher training. A step-by-step onsite teacher training model (SSOTT) in learning the Mathematics has examined through the experimentation to solve the laxity of training up till now. This training involved 30 teachers in Sidoarjo district. Those are divided into three groups. There are two control group and one experiment group. The first group is colled OPOTT, the second is SSOTT, and the third is colled NNT. The result of this training showed that SSOTT model has the better superiority of teacher working than the two groups in control group. Therefore SSOTT can be applied in the Mathematics learning in the special education/school, at least in Sidoarjo district. It is very significant either in the teacher performance or the result of student learning.Keywords: Kinerja guru, pelatihan, dan model SSOTT.